2011
DOI: 10.1111/j.1365-2141.2011.08744.x
|View full text |Cite
|
Sign up to set email alerts
|

Serum selenium concentration at diagnosis and outcome in patients with haematological malignancies

Abstract: SummaryWe have previously reported presentation serum selenium level to be predictive of outcome in diffuse large B-cell lymphoma. This has now been studied in a further 430 patients, 163 with acute myeloid leukaemia (AML), 156 with Hodgkin Lymphoma (HL), and 111 with Follicular Lymphoma (FL). Serum selenium was below the UK normal reference range in 45% of patients, and correlated with serum albumin (r = 0AE24-0AE46, P < 0AE001-0AE003) in all tumour types. Independent predictors of presentation selenium were;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
18
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 30 publications
0
18
0
3
Order By: Relevance
“…In 2011, a further British study confirmed that low Se in serum is associated with a worse outcome in patients with hematological malignancies. However, this association was only present on univariate analysis, suggesting that it reflects other factors [6]. A significant Se deficit has even been shown to correlate to mortality risk in a recent retrospective study with renal cancer patients [7].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In 2011, a further British study confirmed that low Se in serum is associated with a worse outcome in patients with hematological malignancies. However, this association was only present on univariate analysis, suggesting that it reflects other factors [6]. A significant Se deficit has even been shown to correlate to mortality risk in a recent retrospective study with renal cancer patients [7].…”
mentioning
confidence: 99%
“…Se deficiency is associated with a worse outcome in patients with hematological malignancies according to the data from Last et al [4 ]and Stevens et al [6]. In 2010, a German prospective randomized trial showed that Se supplementation with daily doses of 500 µg of sodium selenite during adjuvant radiotherapy is effective in improving blood Se status in Se-deficient cervical and uterine cancer patients, and reduces episodes and the severity of radiotherapy-induced diarrhea.…”
mentioning
confidence: 99%
“…As the paper by Muecke et al [2] in this issue of Acta Haematologica exemplifies, low plasma Se is common in patients with haematological malignancies. Of greater clinical importance, lower serum Se levels are associated with significantly poorer chemotherapy dose delivery, tumour response, and survival [3]. While these associations were not significant on multivariate analysis, the patient numbers were too small to exclude a clinically significant effect.…”
mentioning
confidence: 99%
“…Аналогичные результаты были получены многими авторами при исследовании больных раком матки, яичников, вульвы [18], молочной железы [19], желудочно-кишечного тракта [20] и при гемобластозах [21]. Исследователи полагают, что гипоселенемия может быть обусловлена перераспределением селена в организме в связи с накоплением его в опухолевых клетках [19,21], что ещё раз подтверждает ранее описанное свойство опухоли как "ловушки" жизненно важных метаболитов [22]. Предполагают также, что основным механизмом понижения концентрации селена в крови являются изменения его метаболизма в тканях организма, возникающие при развитии патологического процесса, в том числе и злокачественного [5,21].…”
unclassified
“…Исследователи полагают, что гипоселенемия может быть обусловлена перераспределением селена в организме в связи с накоплением его в опухолевых клетках [19,21], что ещё раз подтверждает ранее описанное свойство опухоли как "ловушки" жизненно важных метаболитов [22]. Предполагают также, что основным механизмом понижения концентрации селена в крови являются изменения его метаболизма в тканях организма, возникающие при развитии патологического процесса, в том числе и злокачественного [5,21]. В то же время следует отметить, что пониженный уровень селена был обнаружен при многих критических состояниях, особенно при полиорганной недостаточности, септических состояниях, системных воспалительных реакциях и других патологиях [4,6,8].…”
unclassified